Phenotypic characterisation of African chickens raised in semi-scavenging conditions - Morris, K.M.; Sutton, K.; Girma, Mekonnen; Esatu, Wondmeneh; Solomon, Bersabhe; Dessie, Tadelle; Vervelde, Lonneke; Psifidi, A.; Hanotte, Olivier H.; Banos, Giorgios (Wageningen University & Research, 2022)
In sub-Saharan Africa, most poultry production is traditional with birds being raised by smallholders in free-range semi-scavenging conditions. The aim of our project is to extensively characterise phenotypes of chickens raised in typical African farming conditions, by measuring production, immunity and survival characteristics. In total, 2,573 chickens were raised in five batches in the poultry facility at ILRI in Ethiopia. These chickens were phenotypically characterised and sampled across an eight-week period. Traits measured included weekly body weight, growth rate, breast muscle weight in carcass, mortality/survival, and immunological titres. The population of chickens had extensive variance at these phenotypes. For body weight, 65% of the total phenotypic variance was attributed to the individual birds providing an excellent source of variation for identifying potential selection markers. This data will subsequently be used along with whole genome sequencing data of these birds to identify selection targets to underpin future breeding programs.